SISTEM PENDUKUNG KEPUTUSAN UNTUK KELAYAKAN PEMBERIAN KREDIT DENGAN METODE FUZZY TSUKAMOTO (STUDI KASUS KOPERASI KEMUNING PERSADA CABANG BANDUNG) - Sri Kurniasih; Lovita Sari Br Ginting (NUANSA INFORMATIKA, 2020)
Koperasi Kemuning Persada (KKP) is one of the companies engaged in lending services, where the main task of the KKP must consider the size of the loan to be given to prospective customers. There is often an error in granting loans to prospective customers because the valuation used is not an objective parameter, especially in terms of determining the size of the proposed loan size, it causes several problems in terms of decisions that must be taken by the relevant branch head. Therefore it is necessary to have a tool or system that can help in terms of decision making of the branch head, related to large / small loans granted. The method used by researchers in designing this Decision Support System is the Fuzzy Tsukamoto method, where the parameters used as criteria in granting credit into 3 (three) things, namely income, collateral and length of business. While the research approach in designing this system uses Object Oriented methodology, assisted with data collection using interview and observation methods. Some tools used to analyze business processes and functional requirements use tools from the Unified Modeling Language (UML), including Usecase diagrams, Sequence Diagrams, Class Diagrams, Activity Diagrams. Applications that researchers design are web-based using the CodeIgniter Framework, programming language uses PHP and HTML while database design uses MySQL.Keywords: SPK, Credit, Fuzzy Tsukamoto